2010
DOI: 10.1111/j.1398-9995.2010.02460.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro evaluation of IgE-mediated hypersensitivity reactions to quinolones

Abstract: Immediate hypersensitivity reactions to quinolones do occur, with moxifloxacin being the drug most frequently involved. The BAT is a useful method for diagnosing patients. Specific IgE was demonstrated by Sepharose-RIA and inhibition assay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
165
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(179 citation statements)
references
References 25 publications
14
165
0
Order By: Relevance
“…The basophil activation test is increasingly used with drugs such as ß-lactams [86], quinolones [57], protein pump inhibitors [87], corticosteroids [56], and ICM [16]. Data obtained in preliminary studies of patients who experienced immediate reactions to ICM have shown promising results.…”
Section: In Vitro Methodsmentioning
confidence: 90%
See 1 more Smart Citation
“…The basophil activation test is increasingly used with drugs such as ß-lactams [86], quinolones [57], protein pump inhibitors [87], corticosteroids [56], and ICM [16]. Data obtained in preliminary studies of patients who experienced immediate reactions to ICM have shown promising results.…”
Section: In Vitro Methodsmentioning
confidence: 90%
“…Some of these patients also react to other ICM to which they had not been previously exposed, probably because the core chemical structure common to ICM is part of the antigenic determinant and thus induces cross-reactivity. Specific IgE to ioxaglate and ioxithalamate has been determined in the sera of patients who experience immediate reactions to ICM using immunoassay techniques [14,51] and basophil activation tests, as reported for many other drugs [56][57][58].…”
Section: Immediate Reactionsmentioning
confidence: 99%
“…25) Similar results were also reported in some positive cases of IgE mediated quinolone allergies. 17) Therefore, it is not clear whether basophil responsiveness is maintained over a long period even in an IgE-mediated reaction, and CD203c expression-based basophil activation test should be performed at the early stages of carboplatin-related HR for more precise results. Further longitudinal follow-up study is needed to confirm the effect of sampling timing on basophil activation test.…”
Section: Discussionmentioning
confidence: 99%
“…[13][14][15][16][17][18] Some researchers suggested that CD203c is more sensitive than CD63 for the diagnosis of drug allergy. 14,20) This may be due to the fact that CD63 is not only a marker of activated basophils but also of platelets and leukocytes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation